LITERATURE REVIEW: PRAKTIK GREEN MARKETING DI BERBAGAI SEKTOR INDUSTRI - Alif Isyawatul Darmawan; Nurul Maghfirah Sultan; Darwis Said; Nadhirah Nagu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to examine green marketing practices across various industrial sectors. A literature review approach used to understand green marketing mechanisms, implemented innovations, consumer segmentation, and evaluation of sustainability-based strategies in each industry. This study summarizes findings from ten reputable scientific articles published between 2021 and 2025, covering the automotive, fashion and textile, cosmetics, food and beverage, tourism, and services (insurance) sectors. The analysis shows that each sector implements a different approach. In the automotive sector, effective strategies include low-emission vehicle innovation and consumer education to build trust in sustainability. In the fashion and textile sectors, innovation in materials and production processes plays a significant role in increasing perceived value and consumer purchase intention. In the cosmetics sector, packaging design and sustainability labeling are dominant factors influencing willingness-to-pay. Meanwhile, in the tourism and services sectors, consumer segmentation and green brand trust are the key aspects in increasing green purchase intention. This research provides a theoretical contribution through a comparative understanding of the implementation and effectiveness of different industries in each sector.